The Urgency of Citizenship Education in the 2013 Curriculum in Class V MI/SD - Farich Alfani, Moch. (CV Kalimasada Group, 2023)
The problems that occur in education in Indonesia include the decrease in the degradation of the character of elementary school students, the use of learning methods that seem difficult for students to understand, are less flexible, less democratic, and tend to be more dominant using one method. For this reason, MI/SD Citizenship Education learning must be strengthened so that in the future it can combine the practice of Pancasila values in everyday life, westernized culture that has permeated Indonesian culture can be minimized starting from styles in speaking, dressing or others. In this study the aims were to describe the urgency of civics education in elementary schools, civics education in the Indonesian context, and the conceptual framework of civic competence in the 2013 curriculum. This study adopted an idea of a descriptive qualitative. the use of techniques applied in this research by taking interview techniques, documentation, and field notes through several stages including data collection, recording, reviewing data sources, and processing information. This research was conducted at MIN 6 Brebes by taking the subjects in this study were fifth grade students and teaching staff who were at MIN 6 Brebes. The urgency of elementary school citizenship education is to prepare young people who understand the contemporary world, play an active role both in solving national and global problems, and to become active contributors to a more just, peaceful, tolerant, safe and sustainable world.